2009
DOI: 10.1111/j.1365-2796.2009.02071.x
|View full text |Cite
|
Sign up to set email alerts
|

B‐type natriuretic peptide and C‐terminal‐pro‐endothelin‐1 for the prediction of severely impaired peak oxygen consumption

Abstract: Objective. To assess the utility of B-type natriuretic peptide (BNP) and C-terminal-pro-endothelin-1 (CTproET-1) to predict a severely impaired peak oxygen consumption (peak VO 2 , < 14 mL kg )1 min )1 ) in patients referred for cardiopulmonary exercise testing.Design. Cross-sectional study.Setting. Tertiary care center.Methods. Peak VO 2 , BNP and CT-proET-1 were assessed in 141 consecutive patients referred for cardiopulmonary exercise testing.Results. B-type natriuretic peptide [median (interquartile range)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Nineteen patients not fulfilling criteria for appropriate effort (see below) were secondarily excluded, leaving 85 patients for the present analysis. The study population represents a subgroup of a population on which we have reported previously [24]. All patients underwent CPET including spirometry and blood gases as well as biomarker measurement in a prospective manner.…”
Section: Methodsmentioning
confidence: 99%
“…Nineteen patients not fulfilling criteria for appropriate effort (see below) were secondarily excluded, leaving 85 patients for the present analysis. The study population represents a subgroup of a population on which we have reported previously [24]. All patients underwent CPET including spirometry and blood gases as well as biomarker measurement in a prospective manner.…”
Section: Methodsmentioning
confidence: 99%